Quantum description of spin tunneling in magnetic molecules - Galetti, D. (Elsevier B.V., 2007)
Starting from a phenomenological Hamiltonian originally written in terms of angular momentum operators we derive a new quantum angle-based Hamiltonian that allows for a discussion on the quantum spin tunneling. The study of the applicability of the present approach, carried out in calculations with a soluble quasi-spin model, shows that we are allowed to use our method in the description of physical systems such as the Mn12-acetate molecule, as well as the octanuclear iron cluster, Fe8, in a reliable way. With the present description the interpretation of the spin tunneling is seen to be direct, the spectra and energy barriers of those systems are obtained, and it is shown that they agree with the experimental ones. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: spin tunneling; Lipkin model; Mn12-acetate; Fe8 cluster